Driving Cocoa Farm Performance through Market Orientation and Institutional Support: The Mediating Role of Innovativeness - Maya Faridhotul Aini; Sri Palupi Prabandari; Radityo Putro Handrito (Journal of Economic Education and Entrepreneurship Studies, 2026)
This study aims to analyze the mechanisms for enhancing cocoa farm performance through the integration of market orientation strategies and institutional support, with a specific focus on the mediating role of farmer innovativeness. By positioning farmers as primary decision-makers underpinned by Upper Echelons Theory, this research explores how individual innovation capacity influences business performance in the upstream sector. Data were collected from 245 smallholder cocoa farmers in Indonesia and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The findings reveal that market orientation exerts a significant positive influence on both farmer innovativeness and business performance. Institutional support, particularly through regulative and cognitive pillars, significantly enhances innovativeness and performance directly. However, the mediation analysis shows that while innovativeness significantly bridges the relationship between market orientation and performance, it does not significantly mediate the link between institutional support and performance. These findings suggest that institutional aid often impacts operational performance directly without necessarily triggering deep-seated innovative transformations. The implications of this research underscore the necessity for policymakers to prioritize human capital development and knowledge infrastructure to foster a more innovative and resilient cocoa agribusiness sector.